Cerebral Cavernous Malformation: Immune and Inflammatory Perspectives - Tu, Tianqi; Peng, Zhenghong; Ren, Jian; Zhang, Hongqi (Frontiers in Immunology, 2022)
Cerebral cavernous malformation(CCM) is a type of vascular anomaly arises due to the dyshomeostasis of brain capillary networks. In the past two decades, many advances have been made in this research field. Notably, as a more reasonable view currently, the CCM lesions should be attributed to the results of a great of additional events related to the homeostasis disorder of endothelial cell. Indeed, one of the most fascinating concerns in the research field is the inflammatory perturbation in the immune microenvironment, which would affect the disease progression as well as the patients’ outcomes. In this work, we focused on this topic, and underlined the immune-related factors’ contribution to the CCM pathologic progression.